RURAL TOURISM DEVELOPMENT BASED ON AGRICULTURAL WISDOM IN METAPHYSICAL ACTIVITIES IN BALI - Kardi, Cening; Pratiwi, Ni Putu Eka (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study explores the development of rural tourism in Bali, rooted in agricultural wisdom and metaphysical practices. It highlights the resilience of rural communities, which remain deeply connected to local wisdom and sustainable agricultural practices. The research emphasizes the significance of rituals and customary ceremonies in agricultural activities, particularly within the Subak system, an indigenous institution that embodies socio-cultural characteristics. The study aims to assess the success of metaphysical agriculture and identify factors influencing it, such as the implementation of Tri Hitha Karana, the effectiveness of customary rules, community relations, and social gatherings. Findings indicate that while the success of metaphysical agriculture is generally at a medium level, there are notable variations in the effectiveness of various factors influencing this success.